Drill Monitoring and GPS Developments and their Impact on the Drill to Mill Process - John Vynne (International Society of Explosives Engineers, 2001)
Too often, a mine’s operations, including drilling, blasting, loading, hauling, crushing, processing, etc., are considered independent steps, rather then a continuous process. In fact, these are interdependent operations with each step in the process having an impact on subsequent operations. If the effectiveness of the drilling and blasting operations can be improved, they will impact the entire mining process. Some of the resulting improvements include: level benches on grade; fragmentation and diggability with the result being reduced loading times; haul cycles improvements; and the crushing and milling operations will be more efficient and less energy consumed. Thunderbird refers to this as “Drill to Mill” information cycle or process. This paper focuses on two of the technological enhancements Thunderbird has added to its drill monitors that allow the mines to impact the “Drill to Mill” concept. These enhancements are: incorporating global positioning satellites into drill monitors; and radio off-loading of data.